2018
DOI: 10.1186/s40643-018-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Light/dark cycle enhancement and energy consumption of tubular microalgal photobioreactors with discrete double inclined ribs

Abstract: Tubular photobioreactors (PBRs) have a great potential in large-scale biomass cultivation and mixers in tubular PBRs have been intensively investigated to achieve high biomass productivity. However, mixers increase not only biomass yield, but also energy consumption. To evaluate performances on increasing light/dark (L/D) cycles and energy consumption of adding a mixer simultaneously, a new parameter named as efficiency of L/D cycle enhancement is introduced. Discrete double inclined ribs, intensively studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, knowing the spectral properties of microalgae could enhance biofuel production by producing more biomass and lipids, although this will depend on improving photobioreactor designs. Models of photobioreactor mixing that have incorporated scalar irradiance [61][62][63][64] and spectral irradiance [65] have shown that continuous mixing in strong light is needed to achieve high biomass production [66]. To enhance biomass and lipid production, the light spectrum could be matched to algal absorption in a well-mixed photobioreactor so that algal cells would experience a high, time-averaged light field with no dead zones to trap cells in suboptimal light levels.…”
Section: Bio-opticsmentioning
confidence: 99%
“…Therefore, knowing the spectral properties of microalgae could enhance biofuel production by producing more biomass and lipids, although this will depend on improving photobioreactor designs. Models of photobioreactor mixing that have incorporated scalar irradiance [61][62][63][64] and spectral irradiance [65] have shown that continuous mixing in strong light is needed to achieve high biomass production [66]. To enhance biomass and lipid production, the light spectrum could be matched to algal absorption in a well-mixed photobioreactor so that algal cells would experience a high, time-averaged light field with no dead zones to trap cells in suboptimal light levels.…”
Section: Bio-opticsmentioning
confidence: 99%
“…The motions of the microalgae particles between the light and dark zones form L/D cycles. A complete duration of the L/D cycle is [22,23,25] t c = t l + t d (13) where t l and t d are the durations for which a particle stays in the light and dark zones [s].…”
Section: The Average L/d Cycle Frequencymentioning
confidence: 99%
“…Gómez-Pérez et al [21] simulated the effect of wall turbulence promoters in a tubular PBR and found that the mixing behavior of the PBR was enhanced after the addition of wall turbulence promoters. Qin et al [22] modified the tube structure and found that the addition of discrete inclined ribs on the tube wall increased the L/D cycle frequency of the algae cells. The highest L/D cycle frequency was obtained when two pairs of ribs with a rib length ratio of 5 were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Designers are always seeking ways to increase algal biomass productivity in PBRs, and the way of introducing mixers to PBRs (including open ponds) has been well developed over the past several decades, such as the trapezoidal chamber mixer in a flat-plate PBR [3], the up–down chute baffles in an open pond [4], the Kenics mixer [5], the plate mixer with a V-groove at the top and a hole at the center [68], the inclined porous mixer [9] and the helical mixer [10] in tubular PBRs. Apart from mixers, novel structures (e.g., the discrete double-inclined ribs in a tubular PBR [11] and a wavy bottom in a pond-like PBR [12]) have also been introduced to PBRs to increase biomass productivity. These novel structures actually serve as mixers for enhancing PBR mixing performance.…”
Section: Introductionmentioning
confidence: 99%